At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Simplify the expressions and find the value:
a) x (x-3) + 2 for x = 2, -1
b)3y (2y - 7) - 3 (y-4) - 63 for y = 1, y = 0


Sagot :

Answer:

[tex]x(x−3)+2=x.x−3x+2 \\ =x2−3x+2 \\F or x=1 \\ putting \:  x=1  \: in \: expression \\ x2−3x+2=(1)2−3(1)+2 \\ =1−3+2 \\ =3−3 \\ =0[/tex]

[tex]Solve  \: 3y(2y−7)−3(y−4)−63 for y=−2 \\ First \: simplify \: it, \\ =6y2−21y−3y+12−63 \\ =6y2−24y−51 \\ Put \:  y=−2 \: =6(−2)2−24(−2)−51 \\ =6×4+48−51 \: 6×4+48−51 \\ 24+48−51 \\ =21[/tex]

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.